1985
DOI: 10.1038/bjc.1985.279
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin A deficiency on the initiation and postinitiation phases of benzo(a)pyrene-induced lung tumourigenesis in rats

Abstract: Summary The present investigation shows the effect of vitamin A deficiency on the initiation and postinitiation phases of benzo(a)pyrene-induced lung carcinogenesis in male Wistar rats. Lung tumours were induced by giving three intratracheal instillations, one week apart, of 10mg benzo(a)pyrene per instillation. Maximum tumour incidence (100%) and tumour burden per rat was found in rats which were kept on vitamin A deficient diet for 4 weeks prior to the first administration and 8 weeks after the last administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Subsequent studies have demonstrated enhanced lung carcinogenesis in vitamin A-deficient animals exposed to the tobacco carcinogen benzo[a]pyrene, possibly due to enhanced binding of the carcinogen to tracheal epithelial DNA. 2,3 These findings have paved the way to vitamin A intervention in experimental lung carcinogenesis. 4,5 The extension of these studies to human lung carcinogenesis and prevention was supported by epidemiologic studies, which suggested that significant dietary intake of vitamin A and carotenoids plays an important role in decreased cancer incidence.…”
Section: An Initial Era Of Optimismmentioning
confidence: 94%
“…Subsequent studies have demonstrated enhanced lung carcinogenesis in vitamin A-deficient animals exposed to the tobacco carcinogen benzo[a]pyrene, possibly due to enhanced binding of the carcinogen to tracheal epithelial DNA. 2,3 These findings have paved the way to vitamin A intervention in experimental lung carcinogenesis. 4,5 The extension of these studies to human lung carcinogenesis and prevention was supported by epidemiologic studies, which suggested that significant dietary intake of vitamin A and carotenoids plays an important role in decreased cancer incidence.…”
Section: An Initial Era Of Optimismmentioning
confidence: 94%
“…Vitamin A deficiency has been reported to cause preneoplastic changes in tracheal [ 3 ] and bronchial epithelium and to be associated with an increased risk of lung cancer [ 4 , 5 ]. The loss of retinoic acid receptor beta (RARβ), one of the vitamin A nuclear receptors, is partly responsible for the lung carcinogenesis in vitamin A deficient individuals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent epidemiological, preclinical and clinical studies established a relationship between vitamin A deficiency and a higher incidence of carcinogenesis in both humans and rodents (Basu, Temple, & Hodgson, 1988; Chaudhy, Jafarey, & Ibrahim, 1980; S. C. Dogra, Khanduja, & Gupta, 1985; Ito, Gajalakshmi, Sasaki, Suzuki, & Shanta, 1999; Stehr, Gloninger, Kuller, Marsh, Radford, & Weinberg, 1985).…”
Section: Cyp26 and Retinoic Acid In Cancermentioning
confidence: 99%